IQ+Programme: Abstract - Bharathraj J; Vidyasagar; Bhavani AD (Journal of All India Institute of Speech and Hearing, 1970)
The IQ   Programme was a small scope research project carried out to put to test the possibility of improving the functioning levels of intelligence among children by using a set of novel training procedures tried for a duration of two months. The experimental group consisted of 8 children varying in age from 5½ to 8 years studying in I, II or II I Standards drawn from a village school. The training procedures were carried out as stipulated in the programme, given by Getman. Four different tests were tried, viz., Seguin Form Board (SFB), Vineland Social Maturity Scale (VSMS),  Columbia Mental Maturity Scale (CMMS) and Kamath's Revision of Binet. A composite Mental Age (MA) inclusive of scores on all the tests with the IQ was worked out both prior to and after the training procedures. The results pointed out a statistically significant improvement by 21 IQ points. The control group did not show any such difference. The findings of the study proved that it is possible to lift up the levels of intellectual functions among children through the use of this procedure.